THE IMPORTANCE OF COMMUNICATIVE GAMES IN ENGLISH LESSONS - Soatov Ibrohimbek; Raimov Olimjon (TADQIQOTLAR, 2025)
Annotation:  This article explores the significant role communicative games play in enhancing the effectiveness of English language lessons. It examines how such games foster student engagement, promote active language use, and create a dynamic classroom atmosphere conducive to learning. The paper highlights the psychological and linguistic benefits of incorporating games, such as reducing anxiety, increasing motivation,  and  improving  speaking  and  listening  skills.  It  also  presents  practical examples of communicative games suitable for various language proficiency levels, offering  valuable  insights  for  teachers  aiming  to  develop  interactive  and  learner-centered  lessons.  The  study  concludes  that  communicative  games  are  not  just supplementary tools but essential strategies for developing students’ communicative competence and confidence in using English.